Cooperation after war - Martin, Eric C. (Managing global transitions, 2006)
This paper discusses how predispositions, incentives, the number and heterogeneity of participants, and leadership (Faerman et al. 2001) jointly influenced the international effort to develop Bosnia and Herzegovina. International coalitions, task forces, and advisory groups are increasingly charged with implementing reforms following civil conflict. This requires a complex web of interorganizational relationships among NGOS, donors and host nations at both global and "ground" levels. To better understand development assistance, attention must be paid to the relationships between these varied players. We find that four factors influenced relationships between policy, donor, and implementing organizations; and those strained relationships, in turn, affected development success. The paper draws on interviews, conducted in Bosnia, with 43 development professionals, observation of development meetings in Tuzla and Sarajevo, and review of related documents from international development programs.
Keywords: Bosna; ekonomski razvoj; mednarodno sodelovanje; razvojni programi; 1995/1999